An Exploratory Step Toward Measuring the "Meaning of Life" in Patients with Tinnitus and in Cochlear Implant Users. - Tyler, Richard; Perreauf, Ann; Mohr, Anne-Mette; Ji, Helena; Mancini, Patricia C. (Journal of the American Academy of Audiology, 2020)
Background Many questionnaires attempt to quantify the "quality of life." However, we believe understanding the quality of life is complex, and many widely used questionnaires do not capture the broad range of factors that we believe are important. Many do not include questions about communicating. Purpose We developed a preliminary questionnaire designed to measure "The Meaning of Life" from a broader perspective. Research Design We reviewed other scales and sought input from individuals with disabilities and developed an initial 23-item questionnaire. Study Sample As a first step, we sampled 116 adults with tinnitus and 196 with cochlear implants (CIs). Individuals who were participating in our CI or tinnitus research programs participated. Data Collection and Analysis To compare differences between the two participant groups, independent sample f-tests were completed for specific items on the questionnaire and for the total score. We compared age and gender differences across all participants using f-tests. Statistical significance was defined as p < 0.05. An exploratory factor analysis was conducted to examine the relationship among the questionnaire items using oblique rotation to produce correlated factors. Extracted factors with an eigenvalue >1.0 were retained according to the Kaiser-Guttman rule. Results Four factors were prominent in this initial sample, which we labeled (1) friendship and positive outlook, (2) physical health, (3) hearing and mental health, and (4) satisfaction with life. Participants with tinnitus reported more trouble sleeping than participants with CI, whereas both groups had lower scores on hearing. Older patients reported more difficulty with remembering things but were more satisfied with their financial situation. Female participants reportedly had more hobbies and were more satisfied with their sex lives than male participants. Conclusions This exploratory study intended to take a broader look at quality of life scales. Further work is needed with a larger sample including younger and older participants with and without disabilities.